Remifentanil inhibits the inflammatory response of BV2 microglia and protects PC12 cells from damage caused by microglia activation. Issue 5 (2nd May 2022) - Huang, Yankui; Cai, Qingxiang; Liu, Huihui; Wang, Yong; Ma, Wuhua
ABSTRACT: Microglia acts as a critical player in neuroinflammation and neuronal injury. Remifentanil (Rem) has been reported to exert anti-inflammatory activity in several types of diseases. However, the role of Rem in microglia-mediated neuroinflammation is unclear. The present study was designed to investigate the effects of Rem against lipopolysaccharide (LPS)-activated BV2 microglial and PC12 cell induced by activated BV2 microglia. Cell proliferative ability was assessed with cell counting kit-8 assay and cellular morphology was observed. ELISA assay was used to measure the expressions of PGE2 and inflammatory factors. The contents of p-NF-KB p65, p-IKKα/β, and COX2 were evaluated with the aid of western blot. The levels of NO and iNOS were assessed with Griess assay, qRT-PCR, and western blot. In addition, Tunel assay and western blot were performed to assess cell apoptosis. The data revealed that Rem alleviated BV2 microglial morphological injury induced by LPS. Furthermore, Rem suppressed inflammatory releases, iNOS, NO and PGE2 stimulated by LPS in activated BV2 cells. Moreover, Rem suppressed PC12 cell injury, the generations of inflammatory factors and cell apoptosis triggered by inflammatory mediators secreted from activated BV2 cells. These results suggest that Rem exhibited anti-neuroinflammatory activity in protecting PC12 cells against injury derived from LPS-stimulated BV2 microglia. Graphical abstract: uf0001